Penalaran Visuospasial Siswa Kategori Intelligence Quotient (IQ) Superior - Suci Wulandari; Elly Susanti; Sri Harini (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
The purpose of this study was to describe the superior intelligence quotient (IQ) category students' visuospatial reasoning. This research was conducted at MAN 1 Trenggalek because the school had already conducted an IQ test. This research uses a qualitative approach with a descriptive exploratory type. The subjects in this study were students who had already done an IQ test with a superior IQ. This study will describe 2 subjects based on relatively the same tendency. Data collection techniques used documentary studies on IQ, test questions, think aloud, and semi-structured interviews. The data analysis in this study refers to Tversky B's research on visuospatial reasoning. The validity of the data in this study used technical triangulation. The results of this study indicate that students with superior IQ are able to meet the indicators of visuospatial reasoning, namely external representation, analysis, synthesis and conclusions as a whole. This is indicated by students with superior IQ who are able to complete the questions according to the procedure and completely.